Increasing compliance with domestic violence protection orders: investing in perpetrator education and support as an investment in victim and family safety - Meyer, Silke (Policing and society, 2022)
Domestic Violence (DV) is a persistent public health issue of global proportions affecting an estimated one in four women worldwide. Civil protection orders or domestic violence orders (DVO) are a legal tool used in many jurisdictions, including Australia, to hold the alleged perpetrators accountable and improve the safety of victims. However, the research on the effectiveness of these orders are mixed and perpetrator non-compliance with such orders continues to be a concern. Few studies examine the situational factors that impact compliance with orders, especially in relation to service engagement and support needs of perpetrators of DV during and beyond the protection order court process. Our study uses focus group data to explore the perceptions of police officers (n = 16) and prosecutors (n = 3) involved in policing and prosecuting DV and the compliance with relevant protection orders in two court districts in Queensland, Australia. Alleged perpetrators’ comprehension of their order conditions and intersecting experiences of social disadvantage and complex needs emerged as key factors influencing compliance, along with the role of timely engagement with alleged perpetrators during the court process to maximise respondent comprehension of order conditions and engagement with available and relevant support services. In concluding, we highlight the importance of protective and preventive aspects of the DVO process that combine holistic wraparound support with perpetrator accountability in order to maximise perpetrator compliance and thus victim and family safety.